Effectiveness of Bankruptcy and Suspension of Obligations for Payment of Debt from Profit and Loss Perspective Compared to Ordinary Law Claims - Halawa, Filemon (CV. Strata Persada Academia, 2023)
After Indonesia was hit by the monetary crisis in the past 1997, the term Bankruptcy & Suspension of Debt Payment Obligations or PKPU was familiar to business actors and to the law. How could it not be, bankruptcy and PKPU are seen as effective ways for creditors to return their collectible rights from debtors who fail to pay their debts. In the midst of global progress in the business world, not a few social problems have arisen. For example, the debt problem of an incapacitated debtor. The question is how to understand bankruptcy & postponement of payment obligations from a profit and loss perspective when compared to an ordinary lawsuit? In this paper, the author provides a general and brief description of how the procedure is for bankruptcy and PKPU applications at the Commercial Court, cassation and judicial review. Including the roles of creditors, debtors, curators, supervisory judges and advocates. Also included is the history of the Commercial Courts in Indonesia and the areas of jurisdiction of commercial courts that have been formed. Not only that, this paper also discusses the pros and cons of whether it is better to use the bankruptcy process or an ordinary lawsuit if a debtor fails to pay his debts when they are due.